KOMPETENSI KEPRIBADIAN GURU PPKN MELALUI KETELADANAN DAN IMPLIKASINYA TERHADAP PEMBENTUKAN KARAKTER DISIPLIN SISWA (STUDI DI SMP NEGERI 1 MOJOLABAN KABUPATEN SUKOHARJO) - Nur Indah Dwi Susanti; Rima Vien Permata Hartanto; Mohammad Muchtarom (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2018)
The objectives of research were (1) to find out the forms of modelling in Personality Competency of Civic Education teacher in SMP Negeri 1 Mojolaban, and (2) to find out the implication of Civic Education teacher’s modelling to creating the students’ discipline character in SMP Negeri 1 Mojolaban. This research employed a qualitative research approach, with descriptive qualitative research type. Data source derived from informant, place, event, and document. The sampling technique used was purposive sampling one. Techniques of collecting data used were interview, observation, and document analysis. Data validation was carried out using data and method triangulations. Data analysis was conducted using an interactive model of analysis. Considering the result of research, the following conclusions could be drawn. (1) The forms of role model in personality competency of Civic Education teacher were as follows: The personality of a disciplined teacher, democratic, patient, tolerant, broad-insight teacher personalities. (2) The implication of Civic Education teachers to the creation of students’ discipline character was as follows: the students could receive and imitate one of Civic Education teachers’ modelling, indicated with their coming early to classroom when the lesson began, students completing school attribute and uniform, students attending the lesson in the classroom and no truancy, students always attending flag ceremony, and maintaining the cleanliness at school. However, role model is the most decisive factor in creating the students’ discipline; it could be seen from the students showing the discipline character only in the classroom Civic Education teachers class VII while the other teacher’s class had not shown the discipline character yet. Keywords: Personality Competency, Civic Education, Modelling, Discipline Chara